Analysis of Australia's fiscal vulnerability to crisis - Gulasekaran Rajaguru; Safdar Ullah Khan; Habib Ur Rahman (Journal of Risk and Financial Management, 2021)
Fiscal vulnerability, like a contagion, poses a threat to financial sector stability, which can lead towards sovereign default. This study aimed to assess fiscal vulnerability to crisis by investigating the Australian economy's gross public debt, net public debt, and net financial liabilities. We used a threshold regression model and compared results with the baseline deficit-debt framework of analysis. The results of the base model suggested that the economy is fiscally sustainable, and that the primary surplus remains unaffected by increasing levels of public debt. In contrast, the threshold regression model indicated that the increasing level of debt has eroded primary surplus below the threshold level of 30.89% of public debt to GDP. These results need further investigation. Therefore, we modified our basic threshold model to capture budget deficit and surplus as a threshold in response to changes in public debt. The results from the sequential threshold regression model using the debt to GDP ratio and primary budget surplus identifying the periods of 1991, 1992, 2008, 2009, 2011 and 2019 as times of likely vulnerability to fiscal crisis. The overall results confirmed that the primary surplus remained sustainable over the estimated threshold level of public debt in all other sample periods and these findings persisted across alternative measures of public debt.
Keywords: 330; Australia; debt to GDP; fiscal sustainability; fiscal vulnerability; primary budget surplus; threshold regression